Advanced Nanocellulose‐Based Composites for Flexible Functional Energy Storage Devices (Adv. Mater. 48/2021). Issue 48 (1st December 2021) - Xu, Ting; Du, Haishun; Liu, Huayu; Liu, Wei; Zhang, Xinyu; Si, Chuanling; Liu, Peiwen; Zhang, Kai
Abstract : Nanocellulose‐Based Composites In article number 2101368, Chuanling Si, Peiwen Liu, Kai Zhang, and co‐workers comprehensively review flexible nanocellulose‐based composites for advanced energystorage systems, such as batteries and supercapacitors. Nanocellulose, with sustainable natural abundance, superb properties, and unique structures, promotes the flexibility, versatility, and ion‐transport dynamics of energy‐storage materials. Nanocellulose‐based composites give rise to energy‐storage devices with outstanding electrochemical performance, flexibility, light weight, and eco‐friendliness for the forthcoming smart‐electronics era.